The Word of Thinking in Intellectual verses of Quran: Exegeses Analysis: قرآنی آیات تفکر میں لفظ "فکر" : تفسیری جائزۃ - Abbasi, Dr. Mohsin Khan; Ahmed, Dr. Imtiaz (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2021)
The Quranic concept of knowledge and intellect is vital for the understanding of Quranic thought and development. Its origin is available in the main stream of Quranic verses. Every single verse is required to rethink every day and build the idea of Muslim faith, social justice, economic growth, and spiritual enhancement. Many verses of the Holy Quran need an explanation for the readers. For this purpose, different commentaries have been written for the understanding of such verses. These commentaries describe different ideas and dimensions for the reader. In this research article, the word "thinking" and some verses related to "thinking" were selected, in order to understand the different approaches mentioned in different commentaries. This article will explore the way forward for the readers to further enhance the idea of Qur’anic word thinking and its uses and development in the Quran and exegeses.